Analisis perilaku Phubbing dan faktor penyebabnya - sarlini, shinta dwi; Yakub, Elni; Mardes, Siska (Peneliti.net, 2023)
Generation Z is currently under threat from the negative impact of technological developments in the form of Phubbing Behavior, therefore the Phubbing phenomenon must immediately receive serious attention and look for what factors cause the Phubbing behavior, this is important to do because the Phubbing Phenomenon has we can see it anywhere, especially in the school environment. The purpose of this study was to determine the level of students' Phubbing Behavior and its causal factors based on gender and grade level. This research uses a type of quantitative descriptive research. the number of respondents in this study totaled 173 male and female students with grade levels 10, 11 and 12. The data collection was carried out through the Phubbing Behavior scale based on the theory and aspects described by Karadag and using the Generic Scale of Phubbing (GSP) scale developed by Chotpitayasunondh and Douglas. A descriptive analysis was then carried out. The results obtained from this study are that the level of Phubbing behavior of students at SMK Bina Profesi Pekanbaru is in the moderate category, then the factors that cause Phubbing behavior in male students are the Nomophobia factor while in female students are the interpersonal conflict factors and the factors that cause Phubbing behavior. based on class level, namely the Interpersonal Conflict factor in grades 10 and 11, and the Nomophobia factor in grade 12. The results of this study can help guidance and counseling teachers in providing treatment to students both in the form of Guidance and Counseling